2021
DOI: 10.5530/ijper.55.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Purple Sweet Potato (Ipomoea batatas L.) Extract-Loaded Carboxymethyl Chitosan and Alginate Nanocapsule in Streptozotocininduced Diabetic Mice

Abstract: Background: Insulin therapy is an essential part in diabetes mellitus type 2 treatment, but it has several side effects such as allergy and hypoglycemia. Therefore, alternative treatments are needed, one of which is by using nanocapsules to increase the performance of the drug delivery system. Purple sweet potato contain high anthocyanin levels which has antidiabetic properties. The idea of this research were to determine the potential use of purple sweet potato extract-loaded CMC-Alginate nanocapsules and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…13,16 Anthocyanins are flavonoid phytopigments with antioxidant properties. 17 Previous research has shown that EDUJ is anti-hyperglycaemic by stimulating the secretion of glucagon-like peptide-1 (GLP-1), the antidiabetic mechanism of anthocyanins by stimulating GLP-1, increatin hormone, and triggering the proliferation of insulin hormone and pancreatic β-cells. 10,17 Saponins have hypoglycemic activity and prevent diabetic complications due to their antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Anthocyanins are flavonoid phytopigments with antioxidant properties. 17 Previous research has shown that EDUJ is anti-hyperglycaemic by stimulating the secretion of glucagon-like peptide-1 (GLP-1), the antidiabetic mechanism of anthocyanins by stimulating GLP-1, increatin hormone, and triggering the proliferation of insulin hormone and pancreatic β-cells. 10,17 Saponins have hypoglycemic activity and prevent diabetic complications due to their antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, I’tishom et al [ 115 ] showed that DM can be treated with carboxymethyl chitosan and alginate nanocapsules loaded with anthocyanin-rich purple-sweet-potato-extract. Researchers found that purple sweet potato extract-loaded chitosan and alginate nanocapsules were 4.4 times more effective at lowering blood glucose levels in diabetic mice caused by Streptozotocin than the extract alone.…”
Section: Application Of Nanotechnology In Dmmentioning
confidence: 99%
“…Besides that, anthocyanin can trigger a potent incretin hormone, also known as glucagon-like peptide-1 (GLP-1). This hormone can stimulate insulin secretion through proliferation and help to keep pancreatic βcells [67], [68].…”
Section: Nutritional Compounds' Mechanismsmentioning
confidence: 99%